GASTRONOMY TOURISM LINKAGE TO LOW CARBON TOURISM - Ongthun, Chakhrit (Academic Journal Phranakhon Rajabhat University, 2021)
Business tourism is a business that plays a vital role and can generate a lot of revenue for Thailand since humans need to travel for new experiences. The growing trend of tourism and driving tourism development in the country. Innovative tourism happens all the time. This article aims to study gastronomy tourism, low carbon tourism, and the link between gastronomy tourism and low carbon tourism utilizing a literature review and related research. Studies have indicated that gastronomy tourism is a consistent approach to low-carbon tourism and activity tours under sustainable tourism. Due to gastronomy, tourism presentation highlighted the social costs of the community, creating economic value through tourism and is also environmentally friendly. The material is part of the local ecology. To promote alternative tourism. To reduce carbon emissions.